2022
DOI: 10.1021/acs.estlett.2c00029
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Processing of Particulate Imidazole Compounds Driven by Photochemistry

Abstract: As a potential fraction of brown carbon, particulate imidazole compounds may initiate photosensitive reactions and have substantial radiative effects. However, our knowledge of the atmospheric processing of imidazole compounds is still in its nascent stage. On the basis of a single-particle aerosol mass spectrometer measurement, the mixing state of imidazole-containing particles and high-time-resolved variations of imidazole compounds were investigated in Qingdao, China, in November and December 2019. Five imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…The concentrations of H 2 O 2 produced by various organic substances during the reaction for 20 min were determined. Considering that, in atmospheric particles, imidazole is usually mixed with sulfate, nitrate, and ammonium, (NH 4 ) 2 SO 4 was used to simulate atmospheric particles, and its deliquescent nature was used to provide a condensed phase for subsequent reactions. Previous studies have demonstrated that H 2 O 2 with a concentration of 1–2 μmol/L spontaneously forms when bulk water is atomized into microdroplets with a diameter of 1–20 μm. , However, the experimental data show that pure (NH 4 ) 2 SO 4 droplets do not form any H 2 O 2 in the dark or the concentration of H 2 O 2 in the collected solution is below the detection limit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of H 2 O 2 produced by various organic substances during the reaction for 20 min were determined. Considering that, in atmospheric particles, imidazole is usually mixed with sulfate, nitrate, and ammonium, (NH 4 ) 2 SO 4 was used to simulate atmospheric particles, and its deliquescent nature was used to provide a condensed phase for subsequent reactions. Previous studies have demonstrated that H 2 O 2 with a concentration of 1–2 μmol/L spontaneously forms when bulk water is atomized into microdroplets with a diameter of 1–20 μm. , However, the experimental data show that pure (NH 4 ) 2 SO 4 droplets do not form any H 2 O 2 in the dark or the concentration of H 2 O 2 in the collected solution is below the detection limit.…”
Section: Resultsmentioning
confidence: 99%
“…substances during the reaction for 20 min were determined. Considering that, in atmospheric particles, imidazole is usually mixed with sulfate, nitrate, and ammonium, 25 (NH 4 ) 2 SO 4 was used to simulate atmospheric particles, and its deliquescent nature was used to provide a condensed phase for subsequent reactions. Previous studies have demonstrated that H 2 O 2 with a concentration of 1−2 μmol/L spontaneously forms when bulk water is atomized into microdroplets with a diameter of 1−20 μm.…”
Section: Photochemical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At low relative humidity (RH), highly concentrated or even supersaturated droplets can form, which enhances reactions with glyoxal. Laboratory studies have shown that imidazole and its derivatives can be byproducts of the reaction of glyoxal (GLY) with nitrogen-containing compounds like amino acids, ammonium ions, or amines, thus contributing to light-absorbing organics or brown carbon (BrC) formation. The atmospheric concentration of imidazole ranges from 0.1 to 14 ng m –3 . , Imidazole compounds, as a significant component of BrC, exhibit potent light-absorbing characteristics that impact the atmospheric radiation balance . Imidazole is typically formed in the particle phase and many oxidants could co-exist in the droplet phase.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole-2-carboxaldehyde (IC), a component of secondary organic aerosol (SOA), has received considerable attention in recent environmental studies due to its photosensitivity and ability to be generated in atmospheric waters. SOA is a group of molecules in the atmosphere that result from the oxidative transformation of volatile organic compounds (VOCs), and it has a substantial impact on air quality, public health, visibility, and climate .…”
Section: Introductionmentioning
confidence: 99%